Local fungal endophytes as rich sources of chitinase genes - Malto, Zabrina Bernice L.; Bacal, Christine Jurene O.; Diaz, Mark Jeffrey S.; Yu, Eizadora T. (2019)
The ability of three fungal endophytes (JB10, JB11, and D12 isolates) to degrade chitin, and their potential as microbial sources of chitinases was investigated. Amplification and sequencing of the ITS regions revealed the identity of the fungal isolates: JB10 (Fomitopsis sp.), JB11 (Aspergillus tubingensis), and D12 (Daldinia eschscholzii). All three fungi were able to grow on minimal media with colloidal chitin as sole carbon source, albeit at different rates. Isolates JB11 and D12 are observed to have comparable or faster growth rates in chitin as compared to the simpler potato dextrose carbon source. Turbidimetric measurements show that the fungal cultures are able to degrade chitin with 3?5 d of incubation. While the crude, secreted proteins from these three fungi show comparable total chitinolytic activities (~0.35 U/mL), JB11 was found to have the highest exochitinase activity (~0.25 U/mL). Bioinformatic analysis of the chitinase (GH18) genes for A. tubingensis (JB11) and D. eschscholzii (D12) revealed variability in the GH18 chitinase sequences in terms of the amino acid sequences of the canonical DXXDXDXE catalytic motif as well as the presence of additional domain architectures, which make these fungi ideal sources for chitinases for both biotechnology applications and chitinase enzyme mechanistic studies. (Author's abstract)